Analisis Kinerja Keuangan Pada Perusahaan Daerah Air Minum (PDAM) Kota Makassar - Randi Tangdialla; Luther P. Tangdialla; Dwi Natalia; Ade Lisa Matasik (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
This study aims to measure and analyze the financial performance of the Municipal Waterworks of Makassar City based on regulation Minister of Home Affairs Indonesia Number 47 of 1999. The data of this study uses secondary data, namely the financial statements from the Municipal Waterworks of the Makassar City in 2015-2017. The method used in this research is quantitative descriptive method. The results show that the measurement of the financial performance of the Municipal Waterworks of Makassar City based on 10 indicators set by the regulation Minister of Home Affairs Indonesia Number 47 of 1999 in 2015 has a financial aspect performance value of 66.67 in the category of